Growth performance, reproductive status, and chromosomal instability in triploid Nile tilapias - Menezes, Williane Ferreira; Alvarenga, Érika Ramos; Nóbrega, Rafael Henrique [UNESP]; França, Luiz Renato; Luz, Marcelo Rezende; Manduca, Ludson Guimarães; Costa, Franklin Fernando Batista da; Bezerra, Vinícius Monteiro; Fernandes, Arthur Francisco de Araújo; Turra, Eduardo Maldonado (FapUNIFESP (SciELO), 2024)
Reproductive control is one of the biggest challenges in tilapia production and triploidy was developed as an alternative to sterilization. In general, polyploids present chromosomal instability but for triploid Nile tilapia it has yet to be reported. This study evaluated the chromosomal instability from juveniles to adulthood, growth performance and gonadal status of tilapia hatched from eggs submitted or not to heat shock for triploid induction. Nile tilapia oocytes were fertilized (1,476 oocytes), half of the eggs were subjected to a four-minute shock in 41 °C water four minutes after fertilization and the other half were not (Control group). The eggs were incubated (at 27°C) and 160 larvae from the treated group hatched and survived after yolk sac absorption. The determination of ploidy was performed by flow cytometry at 85th (juveniles) and 301st (adults) days of age post yolk sac absorption. At the time of the first cytometry analysis there were 73 surviving juveniles from the treated group, and only 14 were confirmed triploid. However, at the analysis of adult ploidy, one out of 8 surviving adult tilapias from the 14 confirmed triploid juveniles remained triploid. Gonadal histology showed that the non-remaining triploids continued to produce gametes. The growth performance of triploid tilapia was initially superior to that of diploid tilapia during the juvenile phase, but similar in adults. Once the chromosome sets are lost and the tilapias become diploid again, at least in tissues with a high proliferation rate, such as the hematopoietic tissue that was analyzed (and possibly in gonads), all possible advantages of triploids are probably lost. Thus, our results suggest that, due to genomic instabilities, the triploid generation of tilapia has low efficiency.
Keywords: genomic instabilities; heat shock; Oreochromis niloticus; polyploidy; reproduction